1986
DOI: 10.1007/bf02676137
|View full text |Cite
|
Sign up to set email alerts
|

Application of silylation to soaps, alcohols and amines in aqueous solutions

Abstract: Gas chromatographic analysis of many surfactants has been limited due to tailing and adsorption of the analyte on the stationary phase of the column by polar groups such as hydroxyl and amine functionalities. Silylation of these surfactants reduces these unfavorable interactions by replacement of the active hydrogen with a silyl group Si-(CHah. Although silylation generally is avoided in aqueous solutions, some surfactants have been silylated successfully in aqueous solutions. These include fatty acids and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…During this procedure Az was found to be relatively insensitive to changes in k,", NO Ak, was chosen as the sole criterion to be minimized. The use of Ak, as the minimization criterion has been reported by other workers (Correa et al, 1987;Zhang and Hill, 1991).…”
Section: I'mentioning
confidence: 84%
See 1 more Smart Citation
“…During this procedure Az was found to be relatively insensitive to changes in k,", NO Ak, was chosen as the sole criterion to be minimized. The use of Ak, as the minimization criterion has been reported by other workers (Correa et al, 1987;Zhang and Hill, 1991).…”
Section: I'mentioning
confidence: 84%
“…The amount of /3-sitosterol and its by-products in the samples was determined with a silylation technique that we have developed on the basis of the work of two earlier workers. Valdez et al (1986) developed a method for the silylation of fatty acids in aqueous solutions. Marks (1988) demonstrated that samples of soybean oil deodorizer distillate could be derivatized by silylation and analyzed by GC without previous saponification or separation of the neutral and acid fractions; however, his method is not applicable to systems containing water.…”
Section: Sample Analysismentioning
confidence: 99%